PENGARUH IMPLEMENTASI ISO 9001:2008 TERHADAP KINERJA MELALUI LINGKUNGAN KERJA DAN DISIPLIN KERJA PEGAWAI PADA UPT PERPUSTAKAAN UNIVERSITAS JEMBER - Nadhifah, Khusnun; Titisari, Purnamie; Prihatini, Dewi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
Abstract: The library of University of Jember (UNEJ) has implemented ISO 9001:2008 Quality Management System (QMS) since 2008. The implementation of ISO 9001:2008 QMS is by increasing the quality of product, service, and employee performance. Therefore, this research aims to significantly analyze the direct influence of ISO 9001:2008 on work environment, work discipline, and employee performance, and the indirect influence of ISO 9001:2008 implementation on employee performance through work environment and work discipline. The sample of this explanatory research consists of 50 respondents, i.e., the employees of UNEJ library. Data were analyzed using path analysis run with SPSS 18. Results show that the implementation of ISO 9001:2008 has a positive and significant influence on work environment, employee discipline, and employee performance; work environment has a positive and significant influence on employee performance; and work discipline has a positive and significant influence on employee performance. Keywords: ISO 9001:2008 Implementation, Work Environment, Work Discipline, Performance.